Relationship Between Mother Characteristics and Parental Feeding Style with Stunting Incidence in Children Under Children - Adela Sari Lubis; Basyariah Lubis (JURNAL KEBIDANAN KESTRA (JKK), 2023)
In 2013, UNICEF stated that 1 in 3 toddlers was stunted. UNICEF data for 2013 states that stunting in Indonesia is predicted to be 7.8 million children under five. This incident places Indonesia in the top 5 countries with the largest number of stunting toddlers in the world. This research aims to analyze the relationship between maternal characteristics and parenting style of feeding with the incidence of stunting. An analytical survey with a cross-sectional approach was chosen in this research. The research was conducted in Palusibaji Village, Pantai Labu District, Deli Serdang Regency in 2022. The population in this study were all mothers who had 56 toddlers and the sampling technique was accidental sampling with a sample of 34 people who were tested using the Chi-Square test at ? = 5%. The research results from the data obtained and based on bivariate analysis, it was concluded that the variables of early breastfeeding initiation (p=0.01), complete basic immunization (p=0.01), and parenting style (p=0.001) are related to the incidence of stunting in toddlers. Analysis of multiple logistic regression tests is parenting style p = 0.003 with a value of Exp (B) = 1.615, which means that parenting styles in good feeding is 1.615 likely not to experience stunting compared to bad parenting styles with stunting events. Conclusion of the study Children who are cared for by parents will find it easier to monitor nutritional intake, feeding patterns, stimulus, and children's activities because parents, especially mothers, care about their children's needs.